Unique Mode of Antiviral Action of a Marine Alkaloid against Ebola Virus and SARS-CoV-2 - Mai Izumida; Osamu Kotani; Hideki Hayashi; Chris Smith; Tsutomu Fukuda; Koushirou Suga; Masatomo Iwao; Fumito Ishibashi; Hironori Sato; Yoshinao Kubo (Viruses, 2022)
Lamellarin α 20-sulfate is a cell-impenetrable marine alkaloid that can suppress infection that is mediated by the envelope glycoprotein of human immunodeficiency virus type 1. We explored the antiviral action and mechanisms of this alkaloid against emerging enveloped RNA viruses that use endocytosis for infection. The alkaloid inhibited the infection of retroviral vectors that had been pseudotyped with the envelope glycoprotein of Ebola virus and SARS-CoV-2. The antiviral effects of lamellarin were independent of the retrovirus Gag-Pol proteins. Interestingly, although heparin and dextran sulfate suppressed the cell attachment of vector particles, lamellarin did not. In silico structural analyses of the trimeric glycoprotein of the Ebola virus disclosed that the principal lamellarin-binding site is confined to a previously unappreciated cavity near the NPC1-binding site and fusion loop, whereas those for heparin and dextran sulfate were dispersed across the attachment and fusion subunits of the glycoproteins. Notably, lamellarin binding to this cavity was augmented under conditions where the pH was 5.0. These results suggest that the final action of the alkaloid against Ebola virus is specific to events following endocytosis, possibly during conformational glycoprotein changes in the acidic environment of endosomes. Our findings highlight the unique biological and physicochemical features of lamellarin α 20-sulfate and should lead to the further use of broadly reactive antivirals to explore the structural mechanisms of virus replication.